Sob as luzes das reformas pombalinas da instrução pública : a produção dicionarística luso-brasileira (1757-1827) - Souza, Álvaro César Pereira de (2011)
This Dissertation has as its objective the analysis of the impact of the so-called Reform of the Public Instruction, carried out by the Marquis of Pombal (1699-1782), on the production of dictionaries of the Portuguese language (monolingual and bilingual) during the period ranging between 1757 and 1827 and how they related with the schooling process, both in Portugal and in Brazil. The year 1757 is taken as the starting point since it was then that the teaching of the Portuguese language was officially institutionalized in Brazil after the enactment of the Lei do Diretorio dos Indios. That law aimed at imposing the Portuguese language and culture on the natives and thus banning the use of their own language, known as general or coastal language. Until then, almost all dictionaries published in the Portuguese language were bilingual (Latin- Portuguese; Portuguese-Latin). As from the Marquis of Pombal s tenure (1750-177) a great number of multilingual dictionaries is seen (Portuguese-Vernacular; Vernacular- Portuguese) until the first completly monolingual dictionary of the Portuguese language is published in 1789: The Diccionario da Lingua Portugueza, by the brazilian lexicographer Antonio de Moraes Silva (1755-1824). Though Moraes Silva s dictionary came to light only after Pombal s government was over we can easily see much of his ideology in his work. The year 1827 represents the setting up of the Schools of First Letters in Brazil. It is observed that an even greater number of dictionaries is produced by this period, which fact suggests the use of these metalinguistic tools for educational purposes both in Portugal and in Brazil. For the development of this work we have consulted the legislation referring to the matter as well as some theorists from the History of Linguistic Ideas (AUROUX, 1992), from the History of School Disciplines (CHERVEL, 1990; HÉBRARD, 1990; 2000), from the Cultural History (ANDERSON, 2008; CHARTIER, 1990; BHABHA, 2006), from the Educational Historiography (ANDRADE, 1978; CARVALHO, 1978; OLIVEIRA, 2010), from the History of the Didactic book (CHOPPIN, 2004) and from the Lexicographic Studies (MESSNER, 1994; VERDELHO, 1982; 2007; SILVESTRE, 2007).